(3LhGH eSGFd GdTQja CHj YRjR bJGOI Hf EOQjSs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3SGd GdSjO GdTQja GdCejQ CHh YRjR bJGOI Hf EOQjS CYRg Gddg JYGdi Yf CQV s
(3BNQgG (B:s
(3EdGCSJdJRehG GdCMcGe hJONdhG ai GdWGYI Je HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3cJHJ HYV GdYfGhjf HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf Ydi GdCchY GdNGUI s
Keywords: (3Gdabg GdESdGejs